2004
DOI: 10.1073/pnas.0400380101
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor suberoylanilide hydroxamic acid reduces acute graft-versus-host disease and preserves graft-versus-leukemia effect

Abstract: Acute graft-versus-host disease (GVHD) and leukemic relapse are the two major obstacles to successful outcomes after allogeneic bone marrow transplantation (BMT), an effective therapy for hematological malignancies. Several studies have demonstrated that the dysregulation of proinflammatory cytokines and the loss of gastrointestinal tract integrity contribute to GVHD, whereas the donor cytotoxic responses are critical for graft-versus-leukemia (GVL) preservation. Suberoylanilide hydroxamic acid (SAHA) is curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
226
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(237 citation statements)
references
References 31 publications
8
226
0
2
Order By: Relevance
“…1C). In addition, consistent with the previous reports (17,18), 0.5 M SAHA showed no inhibition of the donor T cells stimulated with allo-APCs, but 1 M SAHA markedly inhibited the T cell proliferation (Fig. 1D).…”
Section: Saha Augmented Apoptosis and Inhibited Proliferation Of Antisupporting
confidence: 81%
See 2 more Smart Citations
“…1C). In addition, consistent with the previous reports (17,18), 0.5 M SAHA showed no inhibition of the donor T cells stimulated with allo-APCs, but 1 M SAHA markedly inhibited the T cell proliferation (Fig. 1D).…”
Section: Saha Augmented Apoptosis and Inhibited Proliferation Of Antisupporting
confidence: 81%
“…It was reported that an HDAC inhibitor (trichostatin A) represses IL-2 gene expression in anti-CD3 activated T cells (22). Low-dose SAHA treatment resulted in increased acetylation of histone H3 and decreased mRNA levels of IFN-␥ and TNF-␣ in activated spleen cells (17). SAHA treatment also inhibited phosphorylation of STAT1 and STAT3 in response to LPS and alloactivation in vitro (18), and STAT1 and STAT3 play a critical role in the production of proinflammtory cytokines such as IFN-␥ and IL-17 (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent studies suggest that the antileukemic potential of several histone deacetylase (HDAC) inhibitors is dependent upon Akt activation status (Fuino et al, 2003). Thus, the possibility exists that 2ME might interact synergistically with these agents, a number of which are currently in clinical evaluation (Zhou et al, 2002;Reddy et al, 2004). Significantly, HDAC inhibitor lethality has, like 2ME, been attributed to generation of ROS (Rosato et al, 2003).…”
Section: Figurementioning
confidence: 99%
“…Histone deacetylase inhibitors such as suberoylanilide hydroxamic acid (SAHA) have been shown to reduce development of GVHD in murine models by STAT-3 acetylation, which controls indoleamine 2,3-dioxygenasedependent DC functions. [47][48][49] SAHA is currently in clinical trials for the prevention of GVHD. Another potential therapeutic approach to modulate DC tolerance is the development of an antibody to the DC surface maturation antigen CD83; this antibody has been shown to prevent acute GVHD in a humanized mouse model with severe congenital immunodeficiency disorder.…”
Section: Sensors Of Gvhdmentioning
confidence: 99%